REFORMING ONLINE DISPUTE RESOLUTION (ODR) REGULATIONSIN GROWING E-COMMERCE FOR LEGAL CERTAINTY AND PROTECTION - Rohaini, Rohaini; Anjani, Ega; Rusmawati, Dianne Eka; Wardhani, Yulia Kusuma (Universitas Lampung, 2025)
Technological advancements have significantly transformed international trade, particularly through the rapid growth of e-commerce, necessitating effective dispute resolution mechanisms. This research adopts a normative descriptive analytical approach to examine Online Dispute Resolution (ODR) as an integration of Alternative Dispute Resolution (ADR) tailored to address disputes arising in the digital marketplace, with a specific focus on its implementation within the Shopee application. The research first outlines the conceptual framework of ODR and its relevance in the e-commerce context, followed by an analysis of Indonesia’s legal landscape, referencing key regulations such as Law No. 8 of 1999 on Consumer Protection, Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution, and Government Regulation No. 80 of 2019 on Trading Through Electronic Systems. A central contribution of this research lies in its exploration of artificial intelligence (AI) as a problem-solving tool within Shopee’s customer service system, demonstrating how AI can enhance the efficiency, accessibility, and fairness of dispute resolution processes. The research highlights the urgency of establishing a clear regulatory framework for ODR in Indonesia, especially in light of emerging AI-driven solutions that are reshaping the dynamics of e-commerce dispute resolution.